2015
DOI: 10.1371/journal.pone.0129965
|View full text |Cite
|
Sign up to set email alerts
|

Modification by SUMOylation Controls Both the Transcriptional Activity and the Stability of Delta-Lactoferrin

Abstract: Delta-lactoferrin is a transcription factor, the expression of which is downregulated or silenced in case of breast cancer. It possesses antitumoral activities and when it is re-introduced in mammary epithelial cancer cell lines, provokes antiproliferative effects. It is posttranslationally modified and our earlier investigations showed that the O-GlcNAcylation/phosphorylation interplay plays a major role in the regulation of both its stability and transcriptional activity. Here, we report the covalent modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Acetylation at this residue was shown to preclude sumoylation and thereby promote transcriptional activation on a delta-lactoferrin responsive reporter gene. 27 Competition between SUMO and Lys-based ubiquitin modifications has also been observed, usually influencing TF stability (discussed below), but the competition between sumoylation and acetylation often represents a switch between active and inactive forms of modified TFs, with SUMO typically acting as the “off” switch. 26-28 …”
Section: Inhibiting Acetylation and Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetylation at this residue was shown to preclude sumoylation and thereby promote transcriptional activation on a delta-lactoferrin responsive reporter gene. 27 Competition between SUMO and Lys-based ubiquitin modifications has also been observed, usually influencing TF stability (discussed below), but the competition between sumoylation and acetylation often represents a switch between active and inactive forms of modified TFs, with SUMO typically acting as the “off” switch. 26-28 …”
Section: Inhibiting Acetylation and Phosphorylationmentioning
confidence: 99%
“… 55 For delta-lactoferrin and the homeodomain TF ZHX1, sumoylation and ubiquitination are also thought to compete for modification of the same Lys residues, with sumoylation favoring stability of the TFs by blocking ubiquitin-mediated proteolysis. 27,56 In other cases, TF sumoylation inhibits ubiquitination with a consequential increase in TF stability, but whether the modifications compete for the same Lys residues is not yet known (e.g., refs. 57-59 ).…”
Section: Association With and Availability To Bind Chromatinmentioning
confidence: 99%
“…There is crosstalk between SUMOylation and other post-translational modifications (56), and SUMOylation can compete with ubiquitination for substrate lysine residues to prevent proteasome degradation and ensure its stability (57, 58). However, some studies have shown that substrate proteins modified by SUMO as labeled molecules can recruit SUMO-targeted ubiquitin ligases (STUbL) to mediate subsequent ubiquitination degradation (50, 59, 60).…”
Section: Discussionmentioning
confidence: 99%
“…Negative crosstalk may result from the direct competition of two PTMs for the same amino acid or from indirect effects due to one specific PTM masking the recognition site of a second PTM (Hunter, 2007 ). For example, direct competition exists between SUMOylation, ubiquitylation, phosphorylation, and acetylation with ubiquitylation/SUMOylation and SUMOylation/acetylation being mutually exclusive, while SUMOylation/phosphorylation can be agonistic or antagonistic depending on the substrate in question (Escobar-Ramirez et al, 2015 ). Furthermore, the combination of different PTMs on a protein generates a highly regulated interface which may be recognized by specific effector proteins resulting in the controlled initiation of downstream signaling events and facilitating the interactions with diverse binding partners (Sims and Reinberg, 2008 ), thus explaining, for example, how p97 can participate in such a large variety of different cellular functions.…”
Section: Regulation Of P97—cofactor Assemblymentioning
confidence: 99%